2003
DOI: 10.1074/jbc.m308059200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Nuclear Export Signals in Antizyme-1

Abstract: Antizyme-1 (AZ1) is a protein that negatively regulates polyamine synthesis by inhibiting the key synthetic enzyme ornithine decarboxylase and targeting it for degradation by the 26 S proteasome. Recent work shows that antizyme protein translocates to the nucleus during mouse development (Gritli-Linde, A., Nilssom, J., Bohlooly, Y. M., Heby, O., and Linde, A. (2001) Dev. Dyn. 220, 259 -275). However, the significance and mechanism of this phenomenon remain unclear. In this study, we expressed AZ1 fused with en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
1
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 38 publications
(64 reference statements)
7
26
1
1
Order By: Relevance
“…We did not, however, observe a preferential association of GFP-antizyme with one centriole which might be due to non-physiological expression of the fusion protein. Consistent with previous reports (Murai et al, 2003), the GFP-antizyme 1 signal was otherwise mostly cytoplasmic and not nuclear.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…We did not, however, observe a preferential association of GFP-antizyme with one centriole which might be due to non-physiological expression of the fusion protein. Consistent with previous reports (Murai et al, 2003), the GFP-antizyme 1 signal was otherwise mostly cytoplasmic and not nuclear.…”
Section: Resultssupporting
confidence: 92%
“…Treatment with the microtubule-depolymerizing drug nocodazole did not displace the centrosomal antizyme 1 signal demonstrating that the localization of antizyme 1 is microtubule independent (Supplementary data S1). In addition to its centrosomal localization, antizyme 1 was also detected in the nucleus (Figures 1a and d and Supplementary data S1) as reported previously (Murai et al, 2003). The nuclear localization of antizyme 1 was, however, only detected in a fraction of U2OS and NIH-3T3 cells (Figures 1a and d).…”
Section: Resultssupporting
confidence: 85%
“…In accordance with our results with alanine scanning, this substitution resulted in nuclear accumulation of K259N GAPDH (Fig. 6, G and H) (7,(23)(24)(25)(26).…”
Section: Discussionsupporting
confidence: 78%
“…The previous report showed that AZ1 is primarily localized in the nucleus where it transports ODC from the cytosol for degradation by nuclear proteasome (Gritli-Linde et al 2001, Murai et al 2003, Schipper et al 2004. By contrast, we found that AZ1 was mainly localized in the cytosol during conversion of AsPC-1 cells to the differentiated state (Fig.…”
Section: J-i Suzuki Et Al: Glucagon-producing Cell Differentiationcontrasting
confidence: 52%
“…Rat AZ1 has an w85% homology to human AZ1. It expresses a full-length AZ1 without the frameshift because of the deletion of one thymine nucleotide (Murai et al 2003). Transfection was carried out with 4.0 mg plasmid DNA/well using Lipofectamine 2000.…”
Section: Transfection and Stably Expression Of Egfp-rat Az1mentioning
confidence: 99%